KOMPONEN KIMIA DAUN Cinnamomum macrophyllum Miq LAURACEAE - Andria Agusta (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1997)
An analysis on the chemical constituents of Cinnnamomum macrophyllum Miq leaves from Halmahera island using combination techniques GCMS was conducted. Total numbers of the constituents which can be detected were 59 consisted of monoterpenes, sesquiterpenes, aromatic hydrocarbons, phenol derivates, alkanes, oxygenated hydrocarbon, alcohols, aldehydes, carboxylic acid and alkaloid along with eight unidentified compounds (1-8). Leaves of C. macrophyllum contained bioactive compound such as limonene, isoeugenol, methyleugenon, safrole, vitamin E, furfuraldehyde, 2-furan-carboxaldehyde and 7-methyl xanthine.